Áreas protegidas e turismo, estudo de caso: Parque Nacional do Pantanal Motogrossense/MT e seu entorno - Tocantins, Nely (Universidade Federal de São Carlos, 2005)
In Brazil, as in other parts of the world, the appeal of visiting protected areas has significantly grown in the last few years, especially in National Parks which require adequated planning and management action to deal with this increased pressure. This study analyses the types of tourism, and the role of the residents in the immediate surrounding area, which are talking place in the National Park of the Mato Grosso (MT) Pantanal and in the Natural Penha(MS), Acurizal (MS) and Doroché (MT) Private Heritage Reserves, which, for convenience, were given the name of the Pantanal Complex of Protected Areas. This name was used when the area received the titles of World Natural Heritage Site and Biosphere Reserve awarded by UNESCO in the year 2000. The National Park is not open to public visits but the Acurizal Reserve began a pilot Project in 2003 directed towards eco-tourism. ln the area near to the Complex live 20 families, approximately 70 people, who 1Pm off the collection live bait leading to their being known as isqueiros which makes them dependant on fishing tourism in the Iocation. The Complex shows conflicting uses such as amateur and professional fishing, the collecting of live bait, hunting, fires coming from neighboring areas, and the use of its surrounding area for the transport of convoys from the Paraná-Paraguay river route. From these analyses it was possible to propose some control and protection measures that could contribute as an aid to the execution of the Mariagement Plans that are being implemented in these Conservation Units.
Keywords: Conservação da natureza; Parque Nacional Pantanal Matogrossense; Turismo; RPPN; CIENCIAS BIOLOGICAS::ECOLOGIA